-6+4-7-(+7-5-5)+6+(-4+5-3)
You asked:
Evaluate the expression: \(-6 + 4 - 7 - \left(7 - 5 - 5\right) + 6 + -4 + 5 - 3\)
MathBot Answer:
\[-6 + 4 - 7 - \left(7 - 5 - 5\right) + 6 + -4 + 5 - 3 = -2\]
\[\begin{aligned}-6 + 4 - 7 - \left(7 - 5 - 5\right) + 6 + -4 + 5 - 3& = -6 + 4 - 7 - \left(7 - 5 - 5\right) + 6 - 4 + 5 - 3\\& = -6 + 4 - 7 - \left(2 - 5\right) + 6 - 4 + 5 - 3\\& = -6 + 4 - 7 - -3 + 6 - 4 + 5 - 3\\& = -6 + 4 - 7 + 3 + 6 - 4 + 5 - 3\\& = -2 - 7 + 3 + 6 - 4 + 5 - 3\\& = -9 + 3 + 6 - 4 + 5 - 3\\& = -6 + 6 - 4 + 5 - 3\\& = 0 - 4 + 5 - 3\\& = -4 + 5 - 3\\& = 1 - 3\\& = -2\end{aligned}\]